AB1063 INTERSTITIAL LUNG DISEASE IN A NEWBORN AFFECTED BY MEVALONIC ACIDURIA. (June 2019) - Torreggiani, Sofia; Pietrasanta, Carlo; Minoia, Francesca; Filocamo, Giovanni; Ronchi, Andrea; Volpi, Stefano; Caorsi, Roberta; Gattorno, Marco; Caroli, Francesco; Grossi, Alice; Ceccherini, Isabella; Pugni, Lorenza; et al.
Abstract : Background: Mevalonic aciduria (MA) is the most severe phenotype of mevalonate-kinase deficiency (MKD), with early onset and poor prognosis. Given its rarity and its unspecific symptoms, MA diagnosis may be challenging in the newborn. To our knowledge, interstial lung involvement has never been described as onset feature in MKD. Objectives: We report the case of a newborn affected by MKD characterized by interstitial lung disease. Methods: The patient underwent laboratory and radiology evaluation as clinically indicated. Direct Sanger sequencing was used to screen the 10 exons of the MVK gene. Results: A female neonate born at term from consanguineous parents was referred to our hospital at 16 days of life (DOL) for mild hypotonia and persistent raised inflammatory markers despite antibiotic therapy. Infectious work-up was negative. Chest x-ray revealed bilateral perihilar peribronchial thickening. Electroencephalography reported moderate diffuse anomalies of background activity without major abnormalities. On DOL 20 the first episode of fever was recorded. Due to worsening tachypnea and persistent abnormal chest x-ray, a pulmonary CT scan was performed and showed diffuse groundglass bilateral infiltrates consistent with alveolar-interstitial lung disease. On DOL 22 a maculo-papular skin rash appeared on feet and hands, vanishing spontaneously 24 hours later. Bone marrow examination and levels of perforins, neuron-specific enolase and urinary catabolites of catecholamines were normal. A total body MRI was normal except for a mild cerebellar hypoplasia and the known interstitial lung disease. The patient kept presenting hypotonia, relapsing episodes of fever and skin rashes, developed severe anemia and failure to thrive. Type-I IFN signature was negative. A genetic test was requested, as well as quantification of urinary levels of mevalonic acid, which were markedly elevated. Direct Sanger sequencing allowed to detect a homozygous c.709A>T missense mutation in the exon 8 of the MVK gene, coding for a protein substitution p.T237S, classified as pathogenic in the INFEVERS database and therefore consistent with the diagnosis of MKD. Both parents and her sister were heterozygous carriers of the same mutation. On DOL 38 treatment with anakinra was started, with prompt regression of fever and skin rash, decrease in inflammatory markers, increase in reticulocytes count and weight gain. Hypotonia improved but persisted. The patient was discharged from hospital on DOL 56 in good clinical conditions, with acute phase reactants within the normal range and mild hypotonia. She is now 4 months old, still on anakinra treatment without adverse events. Conclusion: Autoinflammatory diseases in the neonatal period are a diagnostic challenge. Clinical suspicion is crucial in order to perform specific laboratory and genetic testing and start appropriate treatment. Interstitial lung involvement may be present in MKD and, together with increased inflammatory markers, could be the first manifestation of the disease. References: [1] Ter Haar NM, et al. The Phenotype and Genotype of Mevalonate Kinase Deficiency: A Series of 114 Cases From the Eurofever Registry. Arthritis Rheumatol. 2016;68:2795-805. [2] Papa R, et al. A web-based collection of genotype-phenotype associations in hereditary recurrent fevers from the Eurofever registry. Orphanet J Rare Dis. 2017;12:167. Disclosure of Interests: Sofia Torreggiani: None declared, Carlo Pietrasanta: None declared, Francesca Minoia: None declared, Giovanni Filocamo: None declared, Andrea Ronchi: None declared, Stefano Volpi: None declared, Roberta Caorsi Consultant for: Novartis, Eli Lilly, Marco Gattorno Grant/research support from: MG has received unrestricted grants from Sobi and Novartis, Francesco Caroli: None declared, Alice Grossi: None declared, Isabella Ceccherini: None declared, Lorenza Pugni: None declared, Fabio Mosca: None declared